1998
DOI: 10.1046/j.1523-1755.1998.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of KS, a novel rat gene expressed exclusively in the kidney

Abstract: KS, a novel rat gene, exhibits a unique tissue-specific expression exclusively in mature kidneys. The data suggest KS may encode an adenosine monophosphate binding enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Some proteins with unknown or doubtful subcellular localization had 90 -100% mitochondrial prediction score with Mitopred or PSORT II (39), such as acid phosphatase 6 (with orthophosphoric monoesters dephosphorylation activity), kidney-specific protein (AMP binding), and ES1 homolog, which is annotated as potentially mitochondrial in the Swiss-Prot database. Interestingly the gene for "kidney-specific protein" that had been described previously to exhibit a unique kidneyspecific expression (40) was also associated with the liver matrix fraction in our study. Due to the high sensitivity of the mass spectrometry, it is likely that trace amounts of proteins were identified and quantitatively relevant in a relatively low protein density sample such as the intermembrane space.…”
Section: Accessionsupporting
confidence: 67%
“…Some proteins with unknown or doubtful subcellular localization had 90 -100% mitochondrial prediction score with Mitopred or PSORT II (39), such as acid phosphatase 6 (with orthophosphoric monoesters dephosphorylation activity), kidney-specific protein (AMP binding), and ES1 homolog, which is annotated as potentially mitochondrial in the Swiss-Prot database. Interestingly the gene for "kidney-specific protein" that had been described previously to exhibit a unique kidneyspecific expression (40) was also associated with the liver matrix fraction in our study. Due to the high sensitivity of the mass spectrometry, it is likely that trace amounts of proteins were identified and quantitatively relevant in a relatively low protein density sample such as the intermembrane space.…”
Section: Accessionsupporting
confidence: 67%
“…We reported previously that renal maturation is delayed by chronic complete UUO. This includes persistence of an immature pattern of glomerular maturation (7,8), microvascular renin distribution (7), and of tubular (25) and interstitial markers (11,38). In the present study, we showed that glomerular maturation is also delayed in the neonatal rat following partial UUO.…”
Section: Discussionsupporting
confidence: 52%
“…A literature review revealed the recent identification of a protein called KS (kidney specific) of the exact size as SA and sharing 55% homology at the amino acid level. 14 Over the epitope used to generate the SA106 antibody, 9/15 amino acids are common between the SA and KS (Figure 4), supporting the likelihood that the absence of SA in the kidneys of SA -/-mice was being obscured by the SA106 antibody binding to KS. This was confirmed by examining protein extracts from the liver, which expresses SA but does not express KS (Figure 3b and Hilgers et al 14 ).…”
Section: Discussionmentioning
confidence: 83%
“…14 Over the epitope used to generate the SA106 antibody, 9/15 amino acids are common between the SA and KS (Figure 4), supporting the likelihood that the absence of SA in the kidneys of SA -/-mice was being obscured by the SA106 antibody binding to KS. This was confirmed by examining protein extracts from the liver, which expresses SA but does not express KS (Figure 3b and Hilgers et al 14 ). Here, a protein of the size for SA was only detected in the livers of SA ϩ/ϩ mice, and again there was no evidence of a truncated protein.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation